Association Of Stunting And Supplementary Feeding In Stunting Prevention Program On Under-Five (6 - 59 Months Old) Children: A Systematic Review - Cleo Syahana Indaryono; Ratna Djuwita; Rita Julianti (Journals of Ners Community, 2022)
The effect of supplementary feeding in stunting prevention programs for toddlers has had mixed results. The purpose of this study was to determine the association of stunting and supplementary feeding in stunting prevention programs in children under five (6 - 59 months): systematic review. subscription database from the University of Indonesia, namely Embase, PUBMED, SAGE, Science Direct, Scopus, and Taylor & Francis. Systematic reviews were extracted and sorted using EndNote and reviewed using Rayyan.ai. The risk of bias was assessed using the Cochrane risk of bias tool. Results: Eight publications meeting the inclusion and exclusion criteria were included in the systematic review and presented qualitatively. Five publications significantly increased LAZ and reduced stunting events over the duration of the study. Conclusion: Five of the eight publications analyzed showed a higher increase in LAZ compared to the controls in each study. Studies show that dual interventions have a higher chance of reducing stunting, and that further research is needed to determine effective and optimal interventions in food absorption through the role of gut health..